2009
DOI: 10.1007/s12272-009-2117-x
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized formulation of olmesartan medoxomil for enhancing oral bioavailability

Abstract: Olmesartan medoxomil (OLM) is an antihypertensive angiotensin II receptor blocker. OLM has a low bioavailability (BA), approximately 26% in humans, due to its low water solubility and efflux by drug resistance pumps in the gastrointestinal tract. Self-microemulsifying drug delivery system (SMEDDS), which is easily emulsified in aqueous media under gentle agitation and digestive motility, was formulated to increase the oral BA of OLM. Among the surfactants and oils studied, Capryol 90, Tween 20, and Tetraglycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…The plasma theophylline level peaked 8 h after oral administration of the formulation, and then slowly declined up to 24 h. The AUC (0-24 h) and AUC (0-¥) were 405 and 415 µg mL -1 h -1 , respectively, and were found to be significantly (p < 0.05) higher than the corresponding values (296.10 and 297.10 µg mL -1 h -1 , respectively) for the commercial product. Although it has been suggested that dissolution of tablets is almost always the rate-limiting step for intestinal absorption (16), this holds for well water soluble and permeable drugs. Dissolution of the drug from tablets controls the pharmacokinetics in case of drugs that fall under the biopharmaceutic classification system (BCS) 1 and 2; BCS 4 drugs possibly depend on dissolution and/or permeability constants.…”
Section: Bioavailability In Rabbitsmentioning
confidence: 99%
“…The plasma theophylline level peaked 8 h after oral administration of the formulation, and then slowly declined up to 24 h. The AUC (0-24 h) and AUC (0-¥) were 405 and 415 µg mL -1 h -1 , respectively, and were found to be significantly (p < 0.05) higher than the corresponding values (296.10 and 297.10 µg mL -1 h -1 , respectively) for the commercial product. Although it has been suggested that dissolution of tablets is almost always the rate-limiting step for intestinal absorption (16), this holds for well water soluble and permeable drugs. Dissolution of the drug from tablets controls the pharmacokinetics in case of drugs that fall under the biopharmaceutic classification system (BCS) 1 and 2; BCS 4 drugs possibly depend on dissolution and/or permeability constants.…”
Section: Bioavailability In Rabbitsmentioning
confidence: 99%
“…Several approaches were investigated to improve the oral bioavailability of OLM, including the development of solid lipid nanoparticles 8 , freezedried solid dispersions 9 , nanosuspensions 10 , nanoemulsions 11 -13 , and self-micro emulsifying drug delivery systems 14 , and solid selfnanoemulsifying drug delivery systems 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These systems can form fine O/W microemulsion droplets (less than 100nm) upon mild agitation and dilution in aqueous media like gastrointestinal fluids. The importance of these systems results from the resultant small droplet size and large surface area; allowing for the enhanced absorption of lipophilic drugs, like OLM, by opening tight junctions to allow Para cellular transport, increasing membrane fluidity to facilitate transcellular absorption, and inhibiting efflux pumps like P-glycoprotein 14,16,17 . Like Nano emulsions, self-nanoemulsifying drug delivery systems (SNEDDS) can be formulated with little energy input (heat or mixing) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…OLM has been formulated as a self-microemulsifying drug delivery system (SMEDDS) using capryol 90, tween 20 and tetraglycol (10:60:30, v/v/v) and Lee and his coworkers reported an improved relative bioavailability of 170% compared to the suspension in male Sprague-Dawley rats (11). SMEDDS as a delivery system have been reported to employ high concentration (30-60%) of surfactants that may lead to cellular toxicity (12).…”
Section: Introductionmentioning
confidence: 99%